A Normative Review of the Integration of Customary Criminal Sanctions into the National Sentencing System for Land Rights Violations - Judy Marria Saimima; Adonia Ivonne Laturette; Juanrico Alfaromona Sumarezs Titahelu (PT. Anagata Sembagi Education, 2026)
The coexistence of customary criminal sanctions and the national sentencing system in Indonesia reflects the country’s plural legal structure, particularly in cases involving land rights violations. While indigenous communities continue to enforce customary sanctions that are socially binding and restorative in nature, Indonesian positive law remains normatively ambiguous regarding their legal status within state-imposed criminal punishment. The enactment of Law No. 1 of 2023 on the National Criminal Code recognizes living law but fails to provide explicit guidance on how customary sanctions should be integrated into sentencing decisions. Using normative legal research with statute, conceptual, and case approaches, this article examines the juridical position of customary criminal sanctions and their implications for legal certainty and proportionality in sentencing. The analysis demonstrates that unregulated coexistence between customary sanctions and state punishment risks inconsistent judicial practices and potential violations of the principle of non bis in idem. This article argues that customary criminal sanctions may only be integrated into the national sentencing system through explicit normative positioning, either as mitigating factors or as regulated corrective measures, in order to uphold legality, legal certainty, and substantive justice in land rights cases.